25-OH vitamin D threshold for optimal bone mineral density in elderly patients with chronic kidney disease - Roy, Debajyoti; Ng, Chee Yong; Kog, Zheng Xi; Yeon, Wenxiang; Poh, Cheng Boon; Koduri, Sreekanth; Chionh, Chang Yin; Sultana, Rehena; Hai Kiat Puar, Troy (Frontiers in Aging, 2022)
Introduction Vitamin D deficiency is common in chronic kidney disease (CKD) and is associated with lower bone mineral density (BMD), decreased muscle strength, and increased hip fracture risk. Guidelines have suggested optimal Vitamin D levels between 20-30ng/ml. However, Vitamin D metabolism is altered in CKD, and optimal levels are unknown. Methods We included 1097 patients with hip fractures. CKD was defined as estimated glomerular filtration rate <60ml/min/1.73m2, and low BMD defined as T score ≤-2.5 at femoral neck. We assessed the utility of using a 25-Vitamin D (25(OH)D) threshold of 30ng/dl, as well as a new threshold, to predict low BMD, in patients with, and without CKD. Results CKD was present in 479 (44%) patients. Using threshold of 25(OH)D <30ng/ml. there was no significant differences in patients with CKD and low BMD, compared to the other groups. We identified 27ng/ml as a better threshold with the Youden index. Using 25(OH)D<27ng/ml as a threshold, 360 of 482 patients (74.7%) with low Vitamin D had low BMD, compared to only 185/276 (67%) of patients with adequate Vitamin D, p=0.02, which was irrespective of presence or absence of CKD. Furthermore, patients with CKD and 25(OH)D <27ng/ml had a higher odds ratio of mortality upon follow-up, 1.61, 95% CI: 1.08 – 2.39, compared to those with CKD and 25(OH)D≥ 27ng/ml.